The digital supply chain - MacCarthy, Bart (Bart L.); Ivanov, Dmitry, 1978- (Amsterdam, Netherlands : Elsevier, 2022)
The Digital Supply Chain is a thorough investigation of the underpinning technologies, systems, platforms and models that enable the design, management, and control of digitally connected supply chains. The book examines the origin, emergence and building blocks of the Digital Supply Chain, showing how and where the virtual and physical supply chain worlds interact. It reviews the enabling technologies that underpin digitally controlled supply chains and examines how the discipline of supply chain management is affected by enhanced digital connectivity, discussing purchasing and procurement, supply chain traceability, performance management, and supply chain cyber security. The book provides a rich set of cases on current digital practices and challenges across a range of industrial and business sectors including the retail, textiles and clothing, the automotive industry, food, shipping and international logistics, and SMEs. It concludes with research frontiers, discussing network science for supply chain analysis, challenges in Blockchain applications and in digital supply chain surveillance, as well as the need to re-conceptualize supply chain strategies for digitally transformed supply chains.
Part 1. Introduction 1. The Digital Supply Chain -- Emergence, Concepts, Definitions, and Technologies Bart MacCarthy and Dmitry Ivanov Part 2. Digital Building Blocks and Enabling Technologies 2. Digital Manufacturing -- The Evolution of Traditional Manufacturing Toward an Automated and Interoperable Smart Manufacturing Ecosystem Dimitris Mourtzis, John Angelopoulos and Nikos Panopoulos 3. Smart Warehouses -- A Sociotechnical Perspective Sven Winkelhaus and Eric H. Grosse 4. The Internet of Things (IoT) -- An Emerging Paradigm to Support the Digitalization of Future Supply Chains Hamed Baziyad, Vahid Kayvanfar and Aseem Kinra 5. The Cloud, Platforms, and Digital Twins -- Enablers of the Digital Supply Chain Gongtao Zhang, Bart L. MacCarthy and Dmitry Ivanov 6. Algorithms, Analytics and Artificial Intelligence -- Harnessing Data to Make Supply Chain Decisions Xavier Brusset, Davide La Torre and Jan Broekaert 7. The Impact of Digitalization on Contemporary and Future Logistics Stephen Pettit, Yingli Wang and Anthony Beresford 8. Blockchain Technologies for the Digital Supply Chain Horst Treiblmaier, Abderahman Rejeb and Wafaa A.H. Ahmed Part 3. Managing the Digital Supply Chain 9. Digital Architectures: Frameworks for Supply Chain Data and Information Governance Konstantina Spanaki, Erisa Karafili and Stella Despoudi 10. Supply Chain Traceability Systems -- Robust Approaches for the Digital Age Kitty Kay Chan 11. Digital Purchasing and Procurement Systems: Evolution and Current State Karsten Cox 12. Measuring and Managing Digital Supply Chain Performance Ashish Kumar Jha, Nishant Kumar Verma and Indranil Bose 13. The Art of Cyber Security in the Digital Supply Chain: Detecting and Defending against Vulnerabilities in your Supply Chain Sang Yoon Cha Part 4. Digital Supply Chain Sectoral Cases 14. Digital Retail -- Key Trends and Developments Lina Zhang and Mikko H anninen 15. Digitalization in the Textiles and Clothing Sector Rudrajeet Pal and Amila Jayarathne 16. Digitalization in Production and Warehousing in Food Supply Chains Fabio Sgarbossa, Anita Romsdal, Olumide Emmanuel Oluyisola andJan Ola Strandhagen 17. Automotive Supply Chain Digitalization: Lessons and Perspectives Nathalie Fabbe-Costes and Lucie Lechaptois 18. Digitalization of the International Shipping and Maritime Logistics Industry- The TradeLens case. Wafaa A.H. Ahmed and Alexa Rios 19. How Can SMEs Participate Successfully in Industry 4.0 Ecosystems? Guilherme Brittes Benitez, N estor Fabi an Ayala and Alejandro Germ an Frank Part 5. Research Frontiers in the Digital Supply Chain 20. Network Science for Supply Chain Analysis -- Theory, Methods, and Empirical Results Guven Demirel 21. Deployment Considerations for Implementing Blockchain Technology in the Pharmaceutical Industry Matthew Liotine 22. Digital Supply Chain Surveillance -- Concepts, Challenges and Frameworks Alexandra Brintrup, Edward Elson Kosasih, Bart MacCarthy and Guven Demirel 23. Sustainability and the Digital Supply Chain Ahmad Beltagui, Breno Nunes and Stefan Gold 24. Re-conceptualizing Supply Chain Strategy for the Digital Era: Achieving Digital Ambidexterity through Dynamic Capabilities Eric Lambourdi ere, Elsa Corbin and J er ome Verny
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on December 27, 2022).
Keywords: Business logistics -- Data processing; Logistique (Organisation) -- Informatique; Business logistics -- Data processing